The implementation of eco-pedagogy-based learning integrated with life skills plays a crucial role in fostering both ecological awareness and personal skills - Putri, Galuh Mentari; Yudianto, Asep; Mustadi, Ali (Journal of Critical Ecology, 2025)
Background: This investigation examines the implementation of eco-pedagogy integrated with life skills education, aiming to strengthen students’ ecological awareness and personal development. Eco-pedagogy in this context supports learners in understanding environmental issues through direct experience, while life skills education helps them develop essential competencies such as communication, responsibility, and decision-making. Together, these approaches position students not only as knowledge recipients but also as active participants in environmental learning and daily-life problem-solving. Methods: The study uses a qualitative approach involving observation, interviews, and documentation to obtain a comprehensive understanding of learning practices. Participants include the school principal, facilitators, staff, parents or guardians, and students. Data analysis applies the Interactive Analysis model by Miles, Saldana, and Huberman, which encompasses data condensation, data display, and conclusion drawing. This method enables systematic interpretation of the learning design, implementation, evaluation, and its overall effectiveness within the school context. Findings: The results show that the independent curriculum and life skills principles. Implementation is flexible and contextual, integrating daily activities such as outing classes, cooking sessions, and practical environmental projects. Assessment uses report cards, portfolios, and talent mapping to capture cognitive, affective, and psychomotor development. Although the program is supported by the foundation, school leaders, and parents or guardians, challenges persist, including limited infrastructure and varying parental understanding of eco-pedagogy concepts. Conclusion: The integration of eco-pedagogy with life skills education positively contributes to the development of ecological awareness, creativity, discipline, independence, and social interaction among students. Learners become more sensitive to environmental issues and more capable of solving daily problems responsibly. Novelty/Originality: This study provides a unique perspective on combining eco-pedagogy and life skills within the independent curriculum, offering insights for schools aiming to adopt similar innovative approaches.